AUDA-NEPAD Gender Climate Change and Agriculture Support Program Training Of Trainers - Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture's contribution to the economy and employment is declining at varying rates, posing various socioeconomic issues. Meeting growing agricultural needs with current farming techniques is expected to lead to over-extraction from natural resources, accelerate greenhouse gas emissions, and low yields. In addition, intensive and unsustainable agriculture will lead to environmental degradation such as loss of biodiversity, deforestation, and land degradation, among other things. Smallholder farmers and especially vulnerable groups like marginalized groups and women are affected the most. In the rural setting, women are left to tend to the family and farm as men relocate to the cities to look for jobs. as a result, this has caused a rise in migratory shifts, particularly among households where the man is the household head. Eventually, this is contributing to gender disparity and associating farming with women. Hence climate-smart agriculture is used to create synergies that will enhance crop production and lead to mitigation and adaption to climate change as well as achieve food security and preserve the environment. Against this backdrop, the gender climate change and agriculture program was initiated in 5 African countries. The GCCASP is funded by Norad and went through several phases of vigorous planning and, subsequently, implementation. The implementation stages of GCCASP are divided into four primary priority intervention areas, which effectively represent different but interconnected sub-programmes: (i) closing policy and institutional gaps, (ii) capacity building of women smallholder farmers, (iii) creation and strengthening of women platforms, and (iv) investments in scaling up successful and innovative practices. The gender climate change and agriculture support program (GCCASP) is meant to be used as a CSA training tool and as a component of the process of improving trainers' and smallholder farmers' capacity to merge CSA practices, innovations, and knowledge by designing and implementing customized training courses at both levels. Various initiatives as well as activities on the ground were carried out during the first stage of implementation. The programs focused on increasing women farmers' capacity through several prioritized training and on Climate-Smart Agriculture (CSA) innovations and practices. The outcomes of this implementation were quite effective, despite some hurdles, such as inadequate finance. this resulted in downscaling and focusing on a small number of districts and stakeholders. Nonetheless, participating countries reported significant outcomes that, when combined with significant resources and a large number of target beneficiaries, might significantly contribute to the African Union Agenda 2063.